Convergence of multisensory inputs in the Xenopus tadpole tectum - Hiramoto, Masateru (2009)
The integration of multisensory information takes place in the optic tectum where visual and auditory/mechanosensory inputs converge and regulate motor outputs. The circuits which integrate multisensory information are poorly understood. In an effort to identify the basic components of a multisensory integrative circuit, we determined the projections of the mechanosensory input from the periphery to the optic tectum and compared their distribution to the retinotectal inputs in Xenopus laevis tadpoles using dye-labelling methods. The peripheral ganglia of the lateral line system project to the ipsilateral hindbrain and the axons representing mechanosensory inputs along the anterior/posterior body axis are mapped along the ventrodorsal axis in the axon tract in the dorsal column of the hindbrain. Hindbrain neurons project axons to the contralateral optic tectum. The neurons from anterior and posterior hindbrain regions project axons to the dorsal and ventral tectum, respectively. While the retinotectal axons project to a superficial lamina in the tectal neuropil, the hindbrain axons project to a deep neuropil layer. Calcium imaging showed that multimodal inputs converge on tectal neurons. The layer specific projections of the hindbrain and retinal axons suggest a functional segregation of sensory inputs to proximal and distal tectal cell dendrites, respectively.